Radical Beings?: how Group Identities Impact Willingness to Justify Terrorism - Løvlien, Eline Drury (Perspectives on terrorism, 2021)
There are many assumptions within terrorism research about the individual characteristics of those who commit or support the use of terrorist tactics, but no larger quantitative study exists on the subject in a European context. To rectify this the article aims to use a group identity framework in a novel way in order to study how group dynamics and group threat impacts individual attitudes toward the use of terrorist tactics. A multilevel research design, using survey data from the European Values Study, is employed to test some of the common explanatory arguments, looking at the role of religion, group identities, and grievances. The findings are mixed, with little support for the argument that religion is a central explanatory factor in understanding radical attitudes. It appears rather that group identities and grievances, as social phenomena, are a more fruitful avenue for understanding why some individuals are more willing to support the use of terrorist tactics. These findings remain robust after controlling for other common explanatory factors and when running alternative model specifications.